Employees Intentions to Use Performance Management System in Regional Bank: Perspective from Generation-X - Saputra, Deddy Eduar Eka; Susita, Dewi; Eliyana, Anis; Pratama, Andika Setia; Muzakki, M Hasyim; Yazid, Zaleha (Aptisi Transactions On Technopreneurship (ATT), 2024)
Amidst a scarcity of literature on the adoption of information technology among Generation X employees within the banking sector, this study aims to delve into the factors influencing their intention to use Performance Management Systems (PMS). Drawing upon the Technology Acceptance Model, this study endeavors to analyze the impact of self-efficacy, perceived usefulness, and attitude towards PMS on the intention to use such systems among Generation X bank employees. Employing a quantitative methodology, the study engaged 158 participants from a regional bank in Indonesia, selected through purposive sampling. Data gathered via online questionnaires underwent analysis using Partial Least Square-Structural Equation Modeling via SmartPLS 4.0 to evaluate ten research hypotheses. The findings revealed that while self-efficacy in PMS did not directly influence the intention to use PMS, perceived usefulness of PMS and attitude to PMS acted as mediators, facilitating the effect of self-efficacy on intention. These results can be attributed to the inherent skepticism and pragmatism of Generation X individuals towards novel technologies. Consequently, this study yields significant insights for both the advancement of technology acceptance literature and the strategic preparedness of banking institutions in adopting new technologies.